Evaluating the efficacy of neoadjuvant immunotherapy combined with chemotherapy for stage IIIa non-small cell lung cancer - Ruiqiang Song; Zhixiang Chen; Tianxi Zheng; Jingfei Huang; Yanbo Cheng (Scientific Reports)
Abstract The prognosis for stage IIIa non-small cell lung cancer (NSCLC) remains poor, necessitating innovative treatment strategies to improve patient outcomes. This study evaluates the efficacy of neoadjuvant immunotherapy combined with chemotherapy in enhancing resection rates, survival, and progression-free survival in patients with stage IIIa NSCLC. A retrospective analysis was conducted on 82 patients treated at The Third People’s Hospital of Zhengzhou, Henan, China, between October 2018 and April 2019. Patients were divided into two groups: an experimental group (n = 41) treated with a combination of platinum-based chemotherapy (pemetrexed and nedaplatin) and the PD-1 inhibitor cindilizumab, and a control group (n = 41) treated with conventional platinum-based chemotherapy. The experimental group demonstrated a significantly higher objective response rate, superior R0 resection rates, and fewer metastatic lymph nodes compared to the control group. Postoperative complications were significantly reduced in the experimental group, accompanied by substantial reductions in tumor markers, including cytokeratin 19 fragments and carbohydrate antigen 125. Median overall survival and progression-free survival were longer in the experimental group than in the control group. Hematological safety was confirmed with no significant differences in routine blood counts between the two groups before or after treatment. These findings support the integration of neoadjuvant immunotherapy and chemotherapy as a promising strategy for treating stage IIIa NSCLC, offering improved resection rates, survival, and reduced complications. Further research is warranted to optimize treatment protocols and validate these results in larger, multicentre studies.